2003
DOI: 10.1074/jbc.m300562200
|View full text |Cite
|
Sign up to set email alerts
|

Poly(dI·dC)-induced Toll-like Receptor 3 (TLR3)-mediated Activation of NFκB and MAP Kinase Is through an Interleukin-1 Receptor-associated Kinase (IRAK)-independent Pathway Employing the Signaling Components TLR3-TRAF6-TAK1-TAB2-PKR

Abstract: Recent studies show that a member of the interleukin-1 (IL-1)/Toll receptor superfamily, Toll-like receptor 3 (TLR3), recognizes double-stranded RNA (dsRNA). Because of the similarity in their cytoplasmic domains, IL-1/Toll receptors share signaling components that associate with the IL-1 receptor, including IL-1 receptorassociated kinase (IRAK), MyD88, and TRAF6. However, we find that, in response to dsRNA, TLR3 can mediate the activation of both NFB and mitogen-activated protein (MAP) kinases in IL-1-unrespo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
244
1
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(250 citation statements)
references
References 53 publications
4
244
1
1
Order By: Relevance
“…48 The dsRNA-activated protein kinase PKR has also been implicated in polyIC-induced NF-kB activation, 49 raising the possibility that dsRNA-induced NF-kB activation may involve PKR and RIP1. Consistent with this model, Jiang et al 50 reported that PKR was recruited to a TRAF6/TAK1/TAB2 complex upon polyIC stimulation. Besides activating NF-kB, this TRAF6/TAK1/TAB2/PKR complex could also activate MKK6 and consequently MAPKs.…”
Section: Role Of Rip1 In Death Receptor Signallingmentioning
confidence: 67%
See 1 more Smart Citation
“…48 The dsRNA-activated protein kinase PKR has also been implicated in polyIC-induced NF-kB activation, 49 raising the possibility that dsRNA-induced NF-kB activation may involve PKR and RIP1. Consistent with this model, Jiang et al 50 reported that PKR was recruited to a TRAF6/TAK1/TAB2 complex upon polyIC stimulation. Besides activating NF-kB, this TRAF6/TAK1/TAB2/PKR complex could also activate MKK6 and consequently MAPKs.…”
Section: Role Of Rip1 In Death Receptor Signallingmentioning
confidence: 67%
“…Besides activating NF-kB, this TRAF6/TAK1/TAB2/PKR complex could also activate MKK6 and consequently MAPKs. 50 Another RIP member, RIP2, also contributes to immune responses upon TLR3 and TLR4 activation. 51 TLR3-and TLR4-induced cell death.…”
Section: Role Of Rip1 In Death Receptor Signallingmentioning
confidence: 99%
“…5,13,14 Together with TRAF6, TAK1 and TAB2, PKR is also recruited to TLR3 upon binding of dsRNA. 25 As seen before with RIP1, 34 the catalytic activity of PKR is not required for NF-kB activation. 35 Similar to RIP1, PKR can activate NF-kB via interaction with TRAFs and the I k B kinase (IKK) complex.…”
Section: Discussionmentioning
confidence: 77%
“…Similar to RIP1, PKR was suggested to participate in TNFRI and TLR3 signaling complex formation leading to NF-kB activation. 25,26 We demonstrated recently the formation of a large molecular weight complex, including RIP1 in Hek293T cell lysates upon incubation at 371C. 27 Therefore, we compared the molecular weights of complexes containing either RIP1 or PKR in the Jurkat E cell extracts following incubation for 1 h at 4 or 371C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation